Izdelava vizualizacije cestnega telesa za potrebe prostorske preveritve - Kovačič, Boštjan (Geodetski vestnik, 2004)
The making of road body visualisation for the needs of spatial verification is most often used prior to construction in order to establish the impacts on the landscape and the environment. Many data are needed for a proper visualisation. These data are acquired with field measurements, digital snapshots, orthophoto snapshots, digitalization and vectorization of the existing data. In the paper, we discuss the visualization methods with the inclusion of the input data, as well as the methods for creating a 3D model. New methods for the making of static and dynamic simulations are also presented.
Keywords: avtoceste; civil engineering; GIS; gradbeništvo; gradnja cest; obdelava podatkov; prostorsko urejanje; vizualizacija